Dynamic spectrum access method for femtocells in LTE - Xu-zhou ZUO; Wei-wei XIA; Lian-feng SHEN (Tongxin xuebao)
Dynamic spectrum access method for femtocells in LTE using cognitive radio method to meet the communication requestions was investigated.An uplink sensing method was proposed.By this method,femtocells could not only identify occupied spectrums but also identify service categories of those spectrums.A dynamic spectrum assess method of power control and frequency hopping for femtocells that ensured a low pre-definable performance impact to macro users was proposed.The femtocell could adopt power control to access the spectrum that carried data service while adopt frequency hopping to access the spectrum that carried voice service.Simulation results show that the downlink throughput of the femtocell can be significantly increased by using proposed spectrum access method.